The teeth of the tiger - Clancy, Tom, 1947- (New York : G.P. Putnam's Sons, 2003)
Jack Ryan, Jr. gets noticed by a firm that seems to have a financial mission, but is really on the lookout for terrorist plots.
Accelerated Reader AR
Keywords: Ryan, Jack (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Children of presidents -- Fiction; Intelligence officers -- Fiction; Fathers and sons -- Fiction; Drug traffic -- Fiction; Suspense fiction